Dampak Lingkungan Bisnis terhadap Keberlangsungan Usaha Dimsum di Kota Medan - Ondo Apostel Purba; Gracia Octaviani Hutagalung; Dina Lestari; Akhlan Naufan Asri; Dionisius Sihombing; Fadli Agus Triansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the relationship between business environment dynamics and the sustainability of microenterprises in the culinary sector, focusing on a case study of dim sum businesses in Medan City. The business environment is conceptualized as a set of external factors, including competitive intensity, local economic conditions, regulations, shifts in consumer preferences, and the strategic role of business location. A qualitative approach was employed using a case study method, with data collected through semi-structured interviews and participant observation of operational activities. The findings indicate that high levels of competition, particularly from new entrants offering lower prices, directly influence the survival strategies of business owners. Adaptive adjustments were implemented through menu innovation, product quality maintenance, and strengthening relationships with loyal customers. Furthermore, the presence of educational institutions and socio-economic activities around business locations supports demand stability, especially from student segments. Strategic physical location enhances both visibility and accessibility but simultaneously intensifies competition. Conceptually, this study highlights that the sustainability of small-scale culinary enterprises is determined not only by internal management capacity but also by the ability to interpret, anticipate, and respond to external dynamics. Consequently, continuous adaptive strategies, product differentiation, and consumer network strengthening are essential prerequisites for culinary micro and small enterprises to maintain competitiveness in a highly competitive market.